A proposed supply chain management model for teacher education institutions: a structural equation modeling - Paguio, Darwin P.; Habib, Md Mamun (© 2017 ExcelingTech Pub, UK., 2018)
This article was published in the International Journal of Supply Chain Management [ © 2017 ExcelingTech Pub, UK. ] The Journal's website is at: http://ojs.excelingtech.co.uk/index.php/IJSCM/article/view/1528